2004
DOI: 10.1007/s00264-004-0540-7
|View full text |Cite
|
Sign up to set email alerts
|

Correction of relapsed or neglected clubfoot using a simple Ilizarov frame

Abstract: We present the results of using a simple Ilizarov fixator frame in treatment of 66 feet in 52 patients (mean age 8.5 years) of 58 relapsed and eight neglected clubfeet with grade III or IV severity with a mean follow-up of 40 (26-58) months. Our frame, in spite of being simple and easy for surgeons and patients to handle, achieved satisfactory correction comparable to the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 11 publications
0
38
0
Order By: Relevance
“…In our study, there was a fixed period of transfixation of midfoot joints in both groups with different previous treatment (Ponseti method and posteromedial release), and we did not find any differences in the postoperative clinical scores or foot angle values even when the patients had scar contracture owing to previous posteromedial release. El Barbary et al [5] also reported that eight of 41 feet with relapsed clubfeet had no previous surgery and there was no difference in correction or recurrence between the different treatment groups. Our patients with soft tissue scars from previous posteromedial release wore the frame for a longer time (mean, 43 versus 34 days) compared with patients who had the Ponseti method.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In our study, there was a fixed period of transfixation of midfoot joints in both groups with different previous treatment (Ponseti method and posteromedial release), and we did not find any differences in the postoperative clinical scores or foot angle values even when the patients had scar contracture owing to previous posteromedial release. El Barbary et al [5] also reported that eight of 41 feet with relapsed clubfeet had no previous surgery and there was no difference in correction or recurrence between the different treatment groups. Our patients with soft tissue scars from previous posteromedial release wore the frame for a longer time (mean, 43 versus 34 days) compared with patients who had the Ponseti method.…”
Section: Discussionmentioning
confidence: 95%
“…The talus is the fulcrum around which the entire foot couples kinematically [19]. Previous studies reported recurrence of foot deformity after removal of the Ilizarov frame even though the Ilizarov frame was maintained for several weeks after full correction of initial foot deformity and a below-knee cast or orthosis also was applied [1,5,8,21,25]. Prem et al [21] reported that 18 of 19 feet with relapsed congenital clubfoot were plantigrade after correction with the Ilizarov frame, but their patients wore the frame for 16 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relapse of the deformity, defined as the child walking on the side of the foot, or when shoe fitting is a problem [11], was noted. Functional results were evaluated according to the Laaveg and Ponseti classification [26].…”
Section: Methodsmentioning
confidence: 99%
“…Major complications associated with wound healing are observed with both types of incision [15]. In order to avoid wound complications, a number procedures such as staged surgery [16], casting with suboptimal correction after surgery followed by serial manipulation [17], expecting secondary healing following partial wound closure [18], or multi-step correction with circular external Wxator may be applied [19][20][21]. In single-step surgery, the risk of wound healing problems is increased on the line of the incision.…”
Section: Discussionmentioning
confidence: 99%